Estrutura de capital, dinamismo ambiental e performance: um estudo no contexto das empresas brasileiras - Fernanda Cintia de Souza (2010)
The performance of the companies is a subject that the attention of financial analysts always deserves, studious and theoretical, for being one of the final objectives of the organizations with lucrative ends. To reach competitive advantages, the companies they search alternativesstrategic to guarantee good performance and need for this deep taking care of to its strategies of investment and financing. The capital structure is understood as the mix of financing that the company uses to carry through its projects and has been one of the studied subjects morein recent years. Allied to the importance of these subjects, the decisions that say respect to the choice of the capital structure must be on to the competitive environment of the firm or, more specifically, to the environmental dynamism, that is, to the degree of instability of thecompetitive environment of the firm. Of this form, the argument is established according to which the capital structure of a company is an organizational element, having, therefore, to be lined up to the degree of dynamism of the competitive environment. The central idea is thatthe impacts of the capital structure on the performance are dependents of the degree of environmental dynamism of the activity sector in which the company operates. The accomplishment of this work had for objective to verify the relation enters the capital structure and the degree of ambient dynamism, as well as its effect on the performance. For this, they had been analyzed given economic-financial of Brazilian companies of capitalopened in the period of 2003 the 2007. The technique of analysis of the data consisted essentially of the accomplishment of an analysis of multiple regression with interaction term. Classification of Economatica® had composed the sample according to a total of 151 companies divided in 16 sectors. The results of the research had allowed to prove the effectmoderator of the environmental dynamism on the relation enter the capital structure and the performance. This study contributes for one better understanding of the decisions of financing from an analysis framework strategic-financial.